The Impact of Trans Papua Road Infrastructure on Local Business Growth in Nduga Regency - Gay Murib; Holomoan Hutajudu; Elsyan R. Marlissa (Review of Multidisciplinary Academic and Practice Studies, 2026)
Purpose: This study examines the impact of road infrastructure development on local business growth in Nduga Regency, Papua Highlands, Indonesia, and explores community perceptions of its economic benefits and its sustainability. Research Methodology: A qualitative descriptive approach, complemented by quantitative analysis (Likert scale), was used to gather primary data from 30 respondents in the Kenyam District, including micro and small entrepreneurs, traders, and community members. Five key informants from the Regional Public Works Agency (PUPR), Bappeda, and community leaders provided additional insights through interviews. Secondary data were obtained from official statistics and government documents from 2019 to 2024. Results: The results show consistently high community ratings across all economic impact indicators, with 83.33% of respondents rating income improvement as "very good," followed by market expansion and trading fluency at 80.00%. Key informant interviews confirmed that road development reduced the prices of basic goods, facilitated trade, and created new business opportunities. Despite these improvements, 79.4% of regency-level roads remain unpaved, and income gains are constrained by limited capital and incomplete road access. Conclusions: The study concludes that road infrastructure is a significant catalyst for economic growth but requires complementary investments in village roads, capital access, and the inclusive participation of Indigenous communities. Limitations: This study had limitations, such as a small sample size and reliance on self-reported data. Contribution: This study provides insights for policymakers and highlights the challenges faced by Indigenous Papuans, offering a foundation for future research on infrastructure development in underserved regions